2005
DOI: 10.1007/s10856-005-6684-1
|View full text |Cite
|
Sign up to set email alerts
|

Laser bonded microjoints between titanium and polyimide for applications in medical implants

Abstract: Bioencapsulation of medical implant devices, and neural implant devices in particular, requires development of reliable hermetic joints between packaging materials that are often dissimilar. Titanium-polyimide is one of the biocompatible material systems, which are of interest to our research groups at Wayne State University and Fraunhofer USA. We have found processing conditions for successful joining of titanium with polyimide using near-infrared diode lasers or fiber lasers along transmission bonding lines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…A. Main et al have been tested laser joined titaniumpolyimide samples for bond strength, andwas observed that the laser bonding parameters such as laser power and feed speed affect the bond strength of all material systems [35]. The applicability of laser joining for a specific material combination and the selection of the appropriate approach depends on the optical properties of the materials.…”
Section: Biomedical and Engineering Application 41 Biomedicalmentioning
confidence: 99%
“…A. Main et al have been tested laser joined titaniumpolyimide samples for bond strength, andwas observed that the laser bonding parameters such as laser power and feed speed affect the bond strength of all material systems [35]. The applicability of laser joining for a specific material combination and the selection of the appropriate approach depends on the optical properties of the materials.…”
Section: Biomedical and Engineering Application 41 Biomedicalmentioning
confidence: 99%
“…4) were loaded in tension in a six-axis submicron tester 4,5,22 for bond strengths. The machine is fully controlled by a computer and can be operated both, in displacement and load controls, along 6 degrees of freedom, i.e.…”
Section: Mechanical Tensile Testsmentioning
confidence: 99%
“…In our previous study, we have analyzed the laser-fabricated titanium/polyimide (TiPI) joints, and observed the presence of a sharp interface based on the creation of chemical bonds between Ti, and O and C contained in PI. 5,6 Titanium is believed to interact primarily with the oxygen double Bonding mechanisms of laser-fabricated microjoints 507 bonds to carbon in the carbonyl groups (>C O), which form part of the PI molecular chains, and to form bonding configurations of the type Ti-O-C. 5,6 In our other related works, we have presented the mechanical characterization of titanium coated glass/polyimide (TiGPI) bonds. 4,7,8 In this case, the glass substrate was coated with a thin titanium layer because the reactivity of titanium with PI was already verified through Refs 5 and 6.…”
Section: Introductionmentioning
confidence: 99%
“…Successful laser joining of metals to plastics has been demonstrated for a range of material combinations. Examples include CFRP-zinc coated steel [4], CFRP-SS304 [5], HDPE-SS304 [6], PA6-SS304 [1], PA66-SS304 [7], PET-A5052 [8,9], PET-AZ91D [10], PET-Cu [9], PET-SS304 [9,[11][12], PET-SS316L [13], PET-Ti [14,15], PMMA-SS304 [16] and PI-Ti [17]. Katayama et al [11] applied continuous wave (CW) diode laser to join SS304 and PET and reported that high strength plastics and metal joints can be fabricated by laser heating due to the formation of mechanical, physical and chemical bonds (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They employed response surface methodology (RSM) to establish mathematical relationships between different process parameters (i.e., laser power, joining speed and stand-off distance) and joint strength. Mian et al [17] applied CW diode, Nd:YAG and fibre lasers to join the Ti with PI. They developed a FEA model to predict the joint strength and the predicted values were in good agreement with the experimental results.…”
Section: Introductionmentioning
confidence: 99%